Methylation associated genes contribute to the favorable prognosis of gliomas with isocitrate dehydrogenase 1 mutation - Liu, Yanwei (Am J Cancer Res, 2015)
Gliomas, the most common primary brain tumors, are characterized by isocitrate dehydrogenase 1 mutation (IDH1-M). High mutation frequency of IDH1 indicates it’s promoting role in tumorgenesis. However, the observation that patients with IDH1-M have better survival comparing with patients with IDH1 wild-type (IDH1-W) suggests that this alteration has other significant beneficial features for patients. Currently, temozolomide (TMZ) is a standard of care for patients which play a major role in DNA methylation that is similar with the role of IDH1-M in genome-wide methylation. In this study, we collected 323 gliomas samples with genome-wide methylation microarray, 502 samples with genome-wide mRNA expression microarray and 295 samples with RNA-seq. By significance analysis of microarray (SAM), we identified 18 genes which are hypermethylation and low expression in samples with IDH1-M comparing with IDH1-W (FDR<0.01). Furthermore, 18 candidate genes were downregulated in TMZ-treated samples. Finally, we obtained two candidate genes, F3 and RBP1. Survival analysis showed that hypermethylation or low expression of the two genes indicated a favorable prognosis, which was consistent with IDH1-M and administration of TMZ in glioma patients. F3 and RBP1 were further validated by qPCR on an independent validation cohort containing 145 samples. Our data suggest that these candidate genes were suppressed by TMZ or IDH1-M induced hypermethylation, resulting in the favorable prognosis of patients with gliomas.